Calcium and Vitamin D Supplementation as Non-Surgical Treatment for Periodontal Disease with a Focus on Female Patients: Literature Review - Zana Sllamniku Dalipi; Fatmir Dragidella (MDPI AG, 2022)
Periodontal disease is a complex disease that involves an imbalance between the oral microbiota and an individual's inflammatory response. Moreover, the inflammatory response contributes to further imbalance; if left untreated, periodontal disease may result in tooth loss. Vitamin D is intricately involved in the regulation of calcium-phosphate homeostasis and bone mineral metabolism; considering that periodontal surgery usually includes regenerative therapy, adequate vitamin D and calcium levels are essential. The benefits of vitamin D and calcium supplementation have been demonstrated in situations where deficiency is associated with adverse outcomes, such as periodontal disease and maternal health. However, knowledge and attitudes about supplementation, as well as the actual levels of supplementation, vary greatly in the general population; they also differ between men and women. The aim of this review is to discuss how vitamin D and calcium supplementation affect oral and periodontal health, especially in women. Additionally, this review provides suggestions for public health strategies regarding vitamin D and calcium supplementation, as well as the effects of both types of supplementation on maternal oral health.